De l’illusion à la culture ou le regard de Winnicott sur la créativité - Sylvie Zérillo (Éducation et Socialisation)
In this article, we want to examine the process through which the infant, searching for the object, goes from illusion to culture. Indeed, at the beginning of life, the primary illusion permits to maintain fusional unity of the nursing-couple, which enables the development of primary creativity. Later, the transitional area, transitional space, where creativity expresses itself through playing, provides the continuity of the relationship—which starts to loosen- between the infant and the mother. Lastly, as a grown-up, the transitional phenomena spread out, leaving space to a cultural area, in which the individual’s creativity expresses itself through the different elements of the cultural field (arts, religion, imaginary life, scientific and creative work . . .). This cultural area allows the subject to create his own relation to reality.